Determinan Kelengkapan Imunisasi Lanjutan Pada Batita di Wilayah Kerja Puskesmas Nanga Pinoh Kabupaten Melawi Tahun 2021 - Dian Indahwati Hapsari; Puspawati; Ria Risti Komala Dewi (Yayasan Literasi Sains Indonesia, 2022)
Follow-up immunization is an activity that aims to ensure that the level of immunity is maintained in children under the age of five, school-aged children, and women of childbearing age (WUS), including pregnant women. Follow-up immunization is the administration of DPT-HB-Hib and rubella measles vaccines. Follow-up immunization coverage in 2018 at the Nanga Pinoh Health Center DPT/HB/Hib 20.8%, MR 25.9%, coverage in 2019 DPT/HB/Hib 28.8%, MR 27.5%, 2020 DPT/HB/ The advanced Hib of 41.4% and the follow-up MR of 37.4% are still far from the set target, which must reach 95%. The purpose of the study was to determine the determinants of the completeness of advanced immunization for toddlers in the working area of the Nanga Pinoh Health Center, Melawi Regency in 2021. This research uses a cross sectional design. The population is toddlers in the working area of the Nanga Pinoh Health Center as many as 941 people, the research sample is 181 taken by proportional random sampling technique. The statistical test used was the chi-square test with a 95% confidence level. The results showed that there was a significant relationship between mother's work (p-value = 0.013), mother's knowledge (p-value = 0.000), mother's behavior (p-value = 0.006), and family support (p-value = 0.008) with follow-up immunizations for toddlers. The unrelated variables were mother's attitude (p-value = 0.087) and support from health workers (p-value = 0.921). It is suggested to the Melawi District Health Office to improve the posyandu cadre training program, provide advice on information communication, home visit programs, and cross-sectoral advocacy, in collaboration with the Puskesmas in counseling and monitoring the follow-up immunization program.